First‐Principles Investigation of Phase Stability in Substoichiometric Zirconium Carbide under High Pressure (Adv. Theory Simul. 12/2022). Issue 12 (11th December 2022) - Thiel, Scott D.; Walsh, James P. S.
Abstract : First‐Principles Investigation of Phase Stability in Substoichiometric Zirconium Carbide under High Pressure Cluster expansion is a powerful data‐driven method that can allow researchers to accurately calculate the energies of millions of structures with outstanding efficiency. In article 2200439, Thiel and Walsh use this method to examine vacancy interactions in ZrC as a function of extreme compression, and show how high pressures could provide a synthetic route to carbon rich phases at synthetically accessible conditions. Artwork created by Chung‐Jui Yu and James P. S. Walsh.